Death of an evangelista - Martin, Allana (Toronto ; New York : Worldwide, 2000)
Detained as a murder suspect after discovering a corpse in a taxi, Texana Jones must prove she is innocent of the crime, which she suspects is related to the shadowy secrets of a respected local family.
"A Texana Jones mystery"--Cover."
Keywords: Jones, Texana (Fictitious character); Women detectives -- Texas; Mexican-American Border Region; Texas